TRANSFORMASI MAHABBAH MENJADI CINTA ABADI DALAM KONSEP TASAWUF BADIUZZAMAN SAID NURSI - Nur Hadi Ihsan; Ridani Faulika Permana; Muhamad Fawwaz Rizaka (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2021)
Abstract Mahabbah or mahabbah Allah (the love of Allah) is the highest spiritual attaintment that Sufis aim for in their spiritual journey. This mahabbah is a form of human love for The Creator which then manifests into love for every beauty and whatever they love. This study will expose Nursi's view of love and how to make human love for everything become eternal. This paper is a library research applying a Sufism approach. The documentary techniques is used to collect the data of this study and the collected data will be analyzed utilizing descriptive-analysis method. This study identifies that according to Nursi, true love is human love for the Creator. This kind of love can only be obtained with ma'rifatullah. If this love for Allah underlies human love for all other than Allah, then he will make all his love eternal. Love for friends, love for wife and children, love for delicious food, love for beauty, and all human love for other than Allah will be eternal if all of them are based and for the sake of Allah.AbstrakMaḥabbah atau lebih tepatnya mahabbah Allah (cinta Allah), merupakan puncak pencapaian spiritual yang hendak dituju oleh para sufi dalam perjalanan spiritual mereka. Mahabbah ini adalah suatu bentuk kecintaan manusia kepada Sang Pencipta yang kemudian manifestasinya menjadi cinta kepada setiap keindahan dan apa saja yang mereka cintai. Kajian ini akan mengungkap pandangan Nursi terhadap cinta dan bagaimana menjadikan cinta manusia kepada segala sesuatu itu menjadi cinta yang abadi. Tulisan ini kajian kepustakaan dengan menggunakan pendekatan tasawuf. Data dalam penelitian ini dikumpulkan menggunakan teknik dokumenter dan data yuang terkumpul akan dianalisis menggunakan metode analisis-deskriptif. Kajian ini mendapati bahwa menurut Nursi, cinta sejati itu adalah cinta manusia kepada Sang Pencipta. Cinta semacam ini hanya dapat dicapai dengan ma'rifatullah. Jika cinta kepada Allah ini mendasari cinta manusia kepada semua selain Allah, maka ia akan menjadikan semua cinta itu abadi. Cinta kepada sahabat, cinta kepada istri dan anak, cinta kepada makanan lezat, cinta kepada keindahan, dan semua cinta manusia kepada selain Allah itu akan menjadi abadi jika semua itu didasari oleh karena cinta kepada, untuk, dan demi Allah.